Research on wide-azimuth seismic advanced detection based on a CO2-concentrated source - Huang, Lanying; Jin, Yuhao; Wang, Shengcheng; Yang, Shuo; Sun, Huachao (Frontiers in Earth Science, 2025)
Conventional seismic advanced detection methods suffer from relatively low lateral resolution and symmetry artifacts in imaging results due to their narrow-azimuth observation systems. To fundamentally solve this problem, starting from a wide-azimuth perspective, constructing a reasonable wide-azimuth observation system is crucial for breaking through the bottleneck of traditional methods. Accordingly, this research investigates wide-azimuth detection utilizing a CO2-concentrated source through theoretical analysis, three-dimensional numerical simulation, and physical analysis. The research results indicate that: (1) Studies establish that the dominant excitation direction for channel wave advanced detection using concentrated force sources is horizontal and perpendicular to the tunnel axis (typically designated the Y direction). The CO2 source controls the excitation direction by adjusting the outlet of the pressure relief head, achieving directional excitation of the concentrated force source. To further identify the seismic wavefield characteristics of this Y-direction concentrated force source, mechanical mechanisms and three-dimensional numerical simulations were adopted. These analyses examined amplitude differences of multi-component P-waves, S-waves, and channel waves across various directions under Y-direction excitation in both homogeneous models and coal-rock-coal models, thereby uncovering the developmental mechanism of channel waves at coal seam interfaces. (2) Based on the Y-direction concentrated force source, a study was conducted on the characteristics of a wide-azimuth three-dimensional three-component seismic wavefield. The reflected trough waves had a large time interval and clear wavefronts compared to other wavefronts in the time domain. The signal-to-noise ratio of seismic records in the Y component is higher than that in the X and Z components, and the reflected trough wave is a characteristic wave for fault detection. (3) The migration processing is carried out using fault characteristic waves. Compared with the narrow-azimuth observation systems, the wide-azimuth observation systems can effectively eliminate symmetry artifacts, further verifying the effectiveness of the method. Comparative experiments were conducted between CO2 seismic sources and explosive seismic sources to further assess the effectiveness of the CO2 source. The frequency spectrum of the CO2 source closely resembles that of the explosive source, with the CO2 source richly exciting high-frequency seismic signals.